The photoshop productivity series : the productive workflow - Cross, Dave; Waitt, Ted (Photoshop productivity series., 2014)
In The Photoshop Productivity Series: The Productive Workflow–the third and final ebook in the three-part "Photoshop Productivity" series by Photoshop guru Dave Cross–Dave teaches you that "workflow" is not nearly as much "work" as it seems, and he avoids the beginning-to-end, step-by-step concept that many people think about when the word "workflow" is mentioned. In fact, he prefers the term "smart flow" to indicate any workflow that takes advantage of the automation capabilities of Photoshop and uses nondestructive, smart techniques to get that work done–and this is what he concentrates on in this ebook. The first concept Dave tackles is working nondestructively, including addressing the use of layers and masks. But why exactly should one work nondestructively? Dave covers that, too, addressing the specific advantages of such a "smart flow": accuracy, creativity, efficiency, and flexibility. Dave then dives deep and tackles vector tools, smart objects, smart filters, and what he calls "smart templates." After working through this final ebook in Dave's Photoshop Productivity series, you will have the skills you need to work smarter–not harder–in Photoshop to get the software to perform what you need, and to do it efficiently, quickly, and nondestructively.